KORUPSI: SIMBOL IDENTITAS - Zainal Arifin (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
Corruption is seen by many experts has become a culture in Indonesia. Various approaches and perspectives of political science try to better understand this issue, but the issue of corruption continue to grow, particularly among officials and members of Parliament. This article tries to give a different understanding about the corruption of katamata anthropology, which views corruption as a form of social reinforcement of group identity